2020
DOI: 10.1111/mpp.12942
|View full text |Cite
|
Sign up to set email alerts
|

Development of FRET‐based high‐throughput screening for viral RNase III inhibitors

Abstract: The class 1 ribonuclease III (RNase III) encoded by Sweet potato chlorotic stunt virus (CSR3) suppresses RNA silencing in plant cells and thereby counters the host antiviral response by cleaving host small interfering RNAs, which are indispensable components of the plant RNA interference (RNAi) pathway. The synergy between sweet potato chlorotic stunt virus and sweet potato feathery mottle virus can reduce crop yields by 90%. Inhibitors of CSR3 might prove efficacious to counter this viral threat, yet no scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
(70 reference statements)
2
3
0
Order By: Relevance
“…Under native Western blotting conditions, CSR3 could be detected as a monomer and a dimer ( Fig. 2D ); under denatured conditions, CSR3 was shown to be primarily monomeric in our previous study ( 24 , 27 ), which is consistent with the results of SDS-PAGE in Fig. 2C .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Under native Western blotting conditions, CSR3 could be detected as a monomer and a dimer ( Fig. 2D ); under denatured conditions, CSR3 was shown to be primarily monomeric in our previous study ( 24 , 27 ), which is consistent with the results of SDS-PAGE in Fig. 2C .…”
Section: Resultssupporting
confidence: 89%
“…These results were consistent with previous studies demonstrating that these four amino acid residues were essential for the catalytic activity of class 1 RNase III (20,23). Moreover, previous studies showed that mutations of CSR3 40E and 44D lead to a loss of function of its endoribonuclease activity on dsRNA and suppression of RNA silencing (15,18,24), confirming their critical function for CSR3 activity.…”
Section: Downloaded Fromsupporting
confidence: 93%
See 3 more Smart Citations